2022
DOI: 10.1039/d2qo00362g
|View full text |Cite
|
Sign up to set email alerts
|

Light-mediated aerobic oxidation of C(sp3)–H bonds by a Ce(iv) hexachloride complex

Abstract: A photochemical C(sp3)–H oxygenation of arene and alkane substrates (including methane) catalyzed by [NEt4]2[CeIVCl6] under mild conditions (1 atm, 25 °C) is described.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 81 publications
0
12
0
Order By: Relevance
“…Chlorine atoms have long been known as a powerful tool for C–H activation yet historically have seen little use in practical applications due to the harsh reaction conditions necessary to generate Cl • . Over the last decade, a number of groundbreaking studies have demonstrated facile chloride oxidation using photoredox catalysts, which have enabled new approaches to functionalize inert C–H bonds. Additionally, environmentally motivated applications rely on chloride oxidation as an important fundamental process for HCl splitting to store solar energy or for electric gradient generation for sea water desalination. However, the vast majority of these examples rely on noble metal photocatalysts to generate chlorine atoms because the one-electron reduction potential, (Cl • /– ), requires an incredibly potent photooxidant. Indeed, chloride ions are so redox inert that they are frequently used as counterions for common photocatalysts such as ruthenium polypyridyl compounds. , Synthesizing ruthenium or iridium coordination compounds that are strong photooxidants requires skillful ligand engineering , and such catalysts often suffer from stability issues. Moreover, photocatalysts based on noble metals are impractical at scale given the low natural abundance of these rare elements. Herein, we report a rare example of light-induced chloride oxidation catalyzed by an inexpensive, commercially available organic photocatalyst through unconventional one- and two-photon pathways.…”
Section: Introductionmentioning
confidence: 99%
“…Chlorine atoms have long been known as a powerful tool for C–H activation yet historically have seen little use in practical applications due to the harsh reaction conditions necessary to generate Cl • . Over the last decade, a number of groundbreaking studies have demonstrated facile chloride oxidation using photoredox catalysts, which have enabled new approaches to functionalize inert C–H bonds. Additionally, environmentally motivated applications rely on chloride oxidation as an important fundamental process for HCl splitting to store solar energy or for electric gradient generation for sea water desalination. However, the vast majority of these examples rely on noble metal photocatalysts to generate chlorine atoms because the one-electron reduction potential, (Cl • /– ), requires an incredibly potent photooxidant. Indeed, chloride ions are so redox inert that they are frequently used as counterions for common photocatalysts such as ruthenium polypyridyl compounds. , Synthesizing ruthenium or iridium coordination compounds that are strong photooxidants requires skillful ligand engineering , and such catalysts often suffer from stability issues. Moreover, photocatalysts based on noble metals are impractical at scale given the low natural abundance of these rare elements. Herein, we report a rare example of light-induced chloride oxidation catalyzed by an inexpensive, commercially available organic photocatalyst through unconventional one- and two-photon pathways.…”
Section: Introductionmentioning
confidence: 99%
“…Photoexcitation to a more reducing excited state 3,75 follows, which leads to C–F cleavage and the generation of an ArCF 2 radical, as supported by experiments with a radical trapping substrate, Scheme 4. The nature of the resulting putative Ln–F species depends on the identity of the rare earth element.…”
Section: Mechanistic Discussionmentioning
confidence: 86%
“…C-F / Ln III (Ln = La, Sm, Yb) interactions have previously been hypothesized in the functionalization of C-F bonds mediated by lanthanide complexes. [37][38][39] Photoexcitation to a more reducing excited state 3,75 follows, which leads to C-F cleavage and the generation of an ArCF 2 radical, as supported by experiments with a radical trapping substrate, Scheme 4. The nature of the resulting putative Ln-F species depends on the identity of the rare earth element.…”
Section: Mechanistic Discussionmentioning
confidence: 87%
“…C–H oxygenation is an attractive strategy for synthesizing value-added oxygenated products (alcohols, aldehydes, and ketones) from cheap alkanes. 74,75 To date, a few PECs adopting this strategy have been successfully established. 76–79…”
Section: Photoanode-mediated Organic Synthesismentioning
confidence: 99%
“…C-H oxygenation is an attractive strategy for synthesizing value-added oxygenated products (alcohols, aldehydes, and ketones) from cheap alkanes. 74,75 To date, a few PECs adopting this strategy have been successfully established. [76][77][78][79] In 2017, Berlinguette and Sammis et al carried out C-H oxygenation at the a-position of the alkene and arene in a PEC taking BiVO 4 as the photoanode.…”
Section: C-h Halogenationmentioning
confidence: 99%